The role of IL-37 in gastrointestinal diseases - Wang, Qiang; Zhang, Guangrun; An, Caiping; Hambly, Brett D.; Bao, Shisan (Frontiers in Immunology, 2024)
Gastrointestinal mucosal surface is frequently under challenge due to it’s the largest surface area and most common entry of microbes. IL-37, an anti-inflammatory cytokine, regulates local and systemic host immunity. H. pylori infection leads to the inhibition of IL-37 in the gastric mucosa, contributing to heightened mucosal inflammation and destruction, thereby facilitating increased proliferation of H. pylori. Food allergy, due to immune dysregulation, also contribute to GI injury. The most updated information is IL-33 On the other hand, elevated levels of IL-37 observed in gastric cancer patients align with reduced host immunity at the cellular and humoral levels, indicating that IL-37 may contribute to the development of gastric cancer via supressing pro-inflammatory responses. While IL-37 provides protection in an IBD animal model, the detection of highly produced IL-37 in IBD patients suggests a stage-dependent role, being protective in acute inflammation but potentially exacerbates the development of IBD in chronic conditions. Moreover, elevated colonic IL-37 in CRC correlates with overall survival time and disease time, indicating a protective role for IL-37 in CRC. The differential regulation and expression of IL-37 between upper- and lower-GI organs may be attributed to variations in the microbial flora. This information suggests that IL-37 could be a potential therapeutic agent, depends on the stage and location.